The impact of the characteristics of the Shari’ah Supervisory Board on the financial performance of Yemeni Islamic banks - AL-aqra'a, Saad Abdullah Ahmed Qasem (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aims to measure the impact of the characteristics of the Shari’a Supervisory Board (SSB) on the financial performance of Yemeni Islamic banks, Through the application on the Islamic banks of Yemen for the period from 2000 to 2016. The study used the descriptive analytical approach using modern techniques of panel data output Eviews version (10). The most important characteristics of the study (SSB size, SSB educational qualification, SSB independent, SSB expertise, SSB cross-membership, change in SSB the composition, SSB Delegation of authority) as independent variables. The rate of return on equity as a independent variable (ROE) represents financial performance. The study adopted the financial reports issued by the Yemeni IFi and the direct field landing to collect other data related to the study. The study found that the variables SSB size, SSB independent, SSB expertise, have a positive impact statistically significant financial performance and the opposite of those variables SSB educational qualification, SSB cross-membership, have a negative impact statistically significant financial performance. The study recommends the necessity of taking into account the optimal size of the Shariah Supervisory Bodies that are compatible with the size of the Islamic Bank and the provision of Shariah bodies with scientists specialized in accounting, finance and economics. In addition to the adoption of a hybrid model, which combines the central and self- model in Islamic banks and other recommendations included in the study.